Analysis of legibility in urban public spaces. Case of El-Alia North-East neighborhood in Biskra, Algeria - Femmam, Nadia; Mazouz, Said (Journal of Applied Engineering Science & Technology, 2018)
The Algerian city faces serious problems related to various dysfunctions, a planned urban structure and a social structure suffering from various social ills. This has a noticeable effect on urban public spaces. The latter are the receptacle of a typology of behaviors, of ways of consuming space that seem to depend on the spatial conformation, the legibility, the identification and the orientation of the user. The present work seeks to explain the relation between legibility and dysfunction in the urban public space and to characterize the influence of space on the movement of pedestrians therefore on their behavior. The selected case study is urban public spaces in the spontaneous neighborhoods of El Alia North-east of the city of Biskra. As a model of analysis, we proposed the combination of two methods obtained from the literature, namely the method of the responsive environments and the method of space syntax. We confronted the results of the analysis of the space syntax and the results of the investigation by the technique of the direct observation "Gate counts". We have shown that the quality of urban public spaces in terms of legibility affects their functioning and their stability.